Predicate-based authenticated key exchange protocol with attribute-hiding - Wen-fen LIU; Jiang-hong WEI; Xue-xian HU (Tongxin xuebao)
To overcome the problem that available predicate-based authenticated key exchange(PBAKE)protocols had drawback on privacy protection,a new PBAKE protocol was presented.The new protocol was constructed via combining an inner product encryption scheme with NAXOS technique.The security of the new protocol could be reduced to GBDH assumption in the modified eCK model.At the same time,for inheriting the security property of attribute-hiding from the inner product encryption scheme,the proposed protocol guarded against disclosure of users’ sensitive information.